The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Emerging Lithographic Technologies VI 2002
DOI: 10.1117/12.472311
|View full text |Cite
|
Sign up to set email alerts
|

Inspection of EUV reticles

Abstract: This paper presents the results of patterned and unpatterned EUV mask inspections. We will show inspection results related to EUV patterned mask design factors that affect inspection tool sensitivity, in particular, EUV absorber material reflectivity, and EUV buffer layer thickness. We have used a DUV (257nm) inspection system to inspect patterned reticles, and have achieved defect size sensitivities on patterned reticles of approximately 80 nm. We have inspected EUV substrates and blanks with a UV (364nm) too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…TaN is more promising than Cr at this point because mask have been made with higher contrast for inspection with TaN (>90%) than with Cr (>65%). 11,43 TaN is also more highly absorbing than Cr at EUV wavelengths, so absorber stacks with TaN can be 5 to 20 nm thinner than those with antireflective Cr. Yan et al 41 recently showed that absorber layers that have index of refraction near unity perform better than those that have an index significantly smaller than unity.…”
Section: Absorber and Buffer Layer Choicementioning
confidence: 98%
See 3 more Smart Citations
“…TaN is more promising than Cr at this point because mask have been made with higher contrast for inspection with TaN (>90%) than with Cr (>65%). 11,43 TaN is also more highly absorbing than Cr at EUV wavelengths, so absorber stacks with TaN can be 5 to 20 nm thinner than those with antireflective Cr. Yan et al 41 recently showed that absorber layers that have index of refraction near unity perform better than those that have an index significantly smaller than unity.…”
Section: Absorber and Buffer Layer Choicementioning
confidence: 98%
“…Pettibone et al 11 have described how contrast and reflectivity of the absorber affect patterned mask inspection sensitivity. The multilayer surface is fairly reflective at typical inspection wavelengths, 43 so the absorber should have low reflectivity to provide high contrast during inspection.…”
Section: Absorber and Buffer Layer Choicementioning
confidence: 98%
See 2 more Smart Citations
“…This provides a contrasted image of the absorber patterns and defects present on top of the mask blank, 4 but this technique is not able to probe the multilayer and image buried defects. 5 Methods based on at-wavelength inspection have already been implemented, and have shown the high potential of this technique. The comparison between at-wavelength bright-field and dark-field measurements shows the advantages and the limits of these two types of techniques.…”
mentioning
confidence: 99%